Methicillin-resistant Staphylococcus aureus in acute otitis externa - Maria J. Duarte (KeAi Communications Co., Ltd., 2018)
Objective: Otologic methicillin-resistant Staphylococcus aureus (MRSA) infection has historically been rare, but given the rise in community-acquired MRSA carriage and infection at other body sites, prevalence rates may be changing. The goal of this study was to determine the prevalence of MRSA in recent otologic cultures from patients with acute otitis externa (AOE). Study design: Retrospective review of an institutional microbiologic database. Methods: A retrospective analysis was performed on serial culture isolates taken from the ear at a quaternary care hospital from January 2014 to April 2016. The causative pathogen and antibiotic sensitivity was determined by culture isolation and end point mean inhibitory concentration (MIC) testing. Medical records were reviewed to document patient characteristics, chronicity of infection, symptomatology, and previous treatments. Results: Over the study period, 173 patients were diagnosed with AOE and underwent otologic cultures of the ear. Fifty-three (30.6%) of cultures grew S. aureus (SA). Of SA infections, 15 (28.3%) were identified as MRSA. MRSA patients were typically older than patients with methicillin-sensitive SA (MSSA) (mean age 46.7 ± 17.9 vs 29 ± 19.4, P = 0.003) and had more medical comorbidities (4 vs 1.7, P = 0.001). Compared to patients with MSSA, patients with MRSA were significantly more likely to have had prior ototopical antibiotic exposure (37% vs 73%, P = 0.019). Conclusion: Contemporary ear culture isolates at quaternary care center show higher rates of MRSA compared to historical reports in the literature. Clinicians should consider ear cultures to identify MRSA AOE. Level of Evidence: IV. Keywords: Acute otitis externa, Staphylococcus aureus, Methicillin-resistant Staphylococcus aureus, MRSA